2009
DOI: 10.1270/jsbbs.59.27
|View full text |Cite
|
Sign up to set email alerts
|

Seed fertility of F1 hybrids between upland rice NERICA cultivars and Oryza sativa L. or O. glaberrima Steud.

Abstract: NERICA (New Rice for Africa) cultivars were crossed with Oryza sativa L. and O. glaberrima Steud. All the F 1 hybrids between NERICA and two strains of O. glaberrima were highly sterile, while the F 1 hybrids of NERICA with two cultivars of O. sativa showed differing levels of fertility depending on the cross combinations. NERICA cultivars were classified into three groups: (1) those compatible with both ssp. indica and ssp. japonica of O. sativa (i.e. NERICA12, NERICA15, NERICA16, NERICA17 and NERICA18); (2) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…Also, a fragrant rice allele BADH2 , which was found in NU1 (Asante et al 2010 ), was located on the three non-parental segments of Chr8: 20379746–20,399,750 in NU1 genotype uniquely as expected (Table 5 ). Ikeda et al ( 2009 ) documented the awnness in NU2 and 5, divergent apiculous color in NU1, 2 and 5, and distinct stigma color in NU1. It appeared that NU2 and 5 conserved CG14 alleles on Regulator of Awn Elongation 1 ( RAEI ), which is one of genes involved in awn formation in CG14 (Furuta et al 2015 ) (Table 5 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, a fragrant rice allele BADH2 , which was found in NU1 (Asante et al 2010 ), was located on the three non-parental segments of Chr8: 20379746–20,399,750 in NU1 genotype uniquely as expected (Table 5 ). Ikeda et al ( 2009 ) documented the awnness in NU2 and 5, divergent apiculous color in NU1, 2 and 5, and distinct stigma color in NU1. It appeared that NU2 and 5 conserved CG14 alleles on Regulator of Awn Elongation 1 ( RAEI ), which is one of genes involved in awn formation in CG14 (Furuta et al 2015 ) (Table 5 ).…”
Section: Resultsmentioning
confidence: 99%
“…81% of our polymorphic sites were on genic regions, and 43% were on promoter regions. In the NU varieties, divergence was observed in quantitative agronomic traits and apparent phenotypes (Ikeda et al 2009 ; Sanni et al 2009 ; Fukuta et al 2012 ; Saito et al 2012 ; Rodenburg et al 2015 ). Studies over the past years have also accumulated data that captures the physiological behavior of the NUs and their divergence in a biotic stress responses (Yamamoto et al 2011 ; Atayese et al, 2016 ; Sikuku et al 2012 ; Sakariyawo et al 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Ikeda et al (2009) revealed that F1 hybrids between NERICA varieties and O. glaberrima are highly sterile. In addition, the F1 hybrids between some NERICA varieties and O. sativa show semi-sterility (Ikeda et al 2009), making it difficult to improve NERICA varieties using conventional breeding processes.…”
Section: Qtl For Hybrid Sterility In Nerica10mentioning
confidence: 99%
“…So far, many NERICA (New Rice for Africa) cultivars have been bred by interspecific hybridization between O. sativa and O. glaberrima (Jones et al 1997;Sarla and Swamy 2005;WARDA 2006). However, in the rice improvement process, hybrid sterility and inviability are major obstacles to the extensive utilization of closely related species in breeding programs and impair the exploitation of the rice genetic diversity and the beneficial effect of the high level of heterosis in these two species (Ikeda et al 2009). …”
Section: Introductionmentioning
confidence: 99%